Grapefruit Production in Open Hydroponics System - Ferrarezi, Rhuanito S.; Nogueira, Thiago A. R. [UNESP]; Jani, Arun D.; Wright, Alan L.; Ritenour, Mark A.; Burton, Randy (Mdpi, 2020)
Conventionally managed citrus orchards can be modified to incorporate advanced horticultural practices such as higher plant density and efficient water and fertilizer application known as open hydroponics system (OHS) to increase productivity under Huanglongbing (HLB) endemic conditions. A field study was conducted from 2013 to 2018 to evaluate the effect of an OHS on Ray Ruby grapefruit (RR) production under HLB-endemic conditions. We tested a combination of different rootstocks [Sour orange (RR/SO) and US-897 (RR/897)], tree planting densities [standard (STD, 358 trees per ha) and high density staggered (HDS, 953 trees per ha)], fertilization methods (dry granular-dry and fertigation-fert), and irrigation systems (double driplines-DD and microsprinkler-MS), arranged in five treatments: RR/SO_STD_dry_MS, RR/SO_HDS_fert_DD, RR/897_HDS_fert_MS, RR/897_HDS_fert_DD, and RR/SO_HDS_fert_MS. All trees were infected byCandidatusLiberibacter asiaticus five years after planting. Trunk diameter and canopy volume increased over time and were higher under RR/SO_STD_dry_MS compared to other treatments. Total fruit number increased in 2016/17 compared to other seasons; however, 65% of fruit were classified as small (<100 mm). Fruit produced under RR/897_HDS_fert_DD had the highest amount (79%) of adequate size fruit (100-117 mm) compared to other treatments. Fruit yield was similar for both rootstocks planted at HDS using DD and MS fertigation, and 67% higher than the standard treatment (RR/SO_STD_dry_MS). Soluble solid contents (SSC), titratable acidity, and SSC-to-titratable acidity ratio were not affected by the treatments. HDS planting resulted in higher fruit yield, irrespective of rootstock and irrigation system, representing an important advance in grapefruit production. Overall, our results demonstrated that production of grapefruit in high-density using OHS can be used by citrus growers who aim to make the best water and fertilizer management under HLB-endemic conditions.
Keywords: Citrus paradisi; citrus nutrition; irrigation management; fruit yield; fruit quality; nutrient use efficiency